The Influence Of "Free Shipping" And Online Customer Reviews On Purchasing Decisions For Shopee Users In Tasikmalaya (Case Study of Fashion Products Shopee Users in Tasikmalaya) - Mustafa, Hana Hawda Sultoni; Pauzy, Depy Muhamad; Risana, Dudu (Jurnal Fokus Manajemen, 2024)
This study aims to analyze the effect of free shipping and online customer reviews, both simultaneously and partially on purchasing decisions for Shopee users in Tasikmalaya. The method used in this research is a quantitative method with a survey approach. The sampling technique is Nonprobability Sampling with the Purprosive Sampling method, the number of samples used is 100 respondents with the criteria that they are Shopee users who live in Tasikmalaya and have made purchases at shopee, especially purchases of fashion products. The data analysis tool used is multiple linear regression with the help of SPSS Version 25 software. The results showed that free shipping and online customer reviews simultaneously had a significant effect on the purchasing decisions of Shopee users in Tasikmlaya. Free shipping and online customer reviews partially have a significant effect on the purchasing decisions of Shopee users in Tasikmalaya.